Suicide and self-harm. Issue 10338 (14th May 2022) - Knipe, Duleeka; Padmanathan, Prianka; Newton-Howes, Giles; Chan, Lai Fong; Kapur, Nav
Summary: Suicide and self-harm are major health and societal issues worldwide, but the greatest burden of both behaviours occurs in low-income and middle-income countries. Although rates of suicide are higher in male than in female individuals, self-harm is more common in female individuals. Rather than having a single cause, suicide and self-harm are the result of a complex interplay of several factors that occur throughout the life course, and vary by gender, age, ethnicity, and geography. Several clinical and public health interventions show promise, although our understanding of their effectiveness has largely originated from high-income countries. Attempting to predict suicide is unlikely to be helpful. Intervention and prevention must include both a clinical and community focus, and every health professional has a crucial part to play.